From sludge incineration ashes to environmentally friendly aggregates - characterization, processing and testing - Tan, Jie Ying (Nanyang Technological University, 2021)
Sewage sludge incineration ash (S-IA) is a by-product generated during the incineration of sewage sludge (SS), a semi solid organic waste generated from the used water (sewage) treatment process. To address the land scarcity challenge and work towards realising Singapore’s vision towards a zero-waste nation, this study explores the possibility of converting S-IA into environmentally friendly aggregates which can be used in the built environment sector in the future. Physical and chemical characterisation were carried out. Various treatment methods were conducted to suppress the leaching of elements of concerned. Different leaching tests were applied to determine the original leaching behaviours of the ashes. The effectiveness of each pretreatment method was evaluated based on the leaching concentration as compared to the regulatory limits. Concrete (mortar) cubes with S-IA mixed with the Ordinary Portland Cement (OPC) were produced and the compressive strength and leaching performance of the cured mortar were determined. S-IA displayed the physical and chemical properties that were close to natural aggregates and demonstrated its potential for uses in civil engineering applications. TCLP leaching results showed that three ashes could be considered hazardous to be landfilled directly as fluoride was not within the Singapore landfill disposal limit. pH-dependent leaching of each element was related to the precipitation or dissolution of oxides or hydroxides under different pH, which generally showed three specific patterns: oxyanionic, cationic and amphoteric. When performing batch leaching with L/S ratios of 2 and 10, it was found that Hg, Mo and sulphate leached significantly, and the S-IA should be classified as hazardous waste based on Waste Acceptance Criteria as specified in the Council Decision 2003/33/EC. Washing, aqueous carbonation and cement stabilization were generally effective in stabilising elements, while dry carbonation only showed an insignificant positive effect on certain elements from certain ashes. Concrete made from partial S-IA substitution with a minimum curing period of 7 days has met the minimum requirement to be used in most of the concrete construction. More research should be done to build confidence in publics and stakeholders in reusing S-IA in the built environmental sector while bringing environmental and economic benefits compared to using conventional construction materials.